The epidemiology of injury among adolescents with hearing loss, health beliefs regarding injury and associated factors - GÜR, KAMER (ELSEVIER SCIENCE INC, 2021)
Background: Adolescents with hearing loss are more at risk of injury. Their injuries commonly occur at school, in traffic, and other sporting areas and can adversely affect their health. Objective: The study aims were to understand the epidemiology of the injuries that occurred among adolescents with hearing loss and to explore their health beliefs regarding injury and their associated factors. Methods: A cross-sectional study was conducted over the period 2018-2019 with 218 adolescents with hearing loss. A sociodemographic questionnaire, an accident and knowledge questionnaire, the Health Belief Model (HBM)-based Injury Scale and a school accident form were provided by interviewers who were fluent in sign language. Descriptive statistics, the Mann-Whitney U, Kruskal-Wallis tests and regression analysis were used to analyze the responses given to the above instruments. Results: Forty-six percent of the adolescents with hearing loss experienced accidents, with pedestrian (42.9%) and passenger (42.9%) types being the most common traffic-related injuries and bleeding (29.4%) and fracture (23.5%) for school related injuries. Factors that are protective against injuries are higher parental education level (father education: OR 1.08, 95% CI = 0.81-1.44; mother education: OR 0.77, 95% CI = 0.59-1.01), and higher knowledge of traffic signs (right: OR 1.23, 95% CI = 0.62-2.42; green: OR 0.59, 95% CI = 0.28-1.23). Factors that were associated with elevated risk of injuries included worse hearing loss categories (OR 3.39, 95% CI = 1.07-8.99). Conclusions: Adolescents with hearing loss are commonly injured. Schools should consider education on how adolescents with hearing loss can protect themselves through potential tailored HBM-based injury prevention interventions. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: Hearing loss; Adolescent; Injury; Health belief